1989
DOI: 10.1002/star.19890410402
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Physicochemical, Pasting Characteristics and Amylolytic Susceptibility of Starch from Sorghum (Sorghum bicolor L. Moench) Grains

Abstract: Preparation, physicochemical properties, pasting behavior and amylolytic susceptibility of sorghum starch have been investigated. The yield of starch was about 60.25%, on whole grain basis. The starch exhibited double stage swelling and low solubility pattern in an aqueous system. Viscoamylographic studies on pasting behaviour of the starch revealed a peak viscosity of 800 B. U. at 8% (w/v) concentration; however, it decreased considerably during cooking (viz.holding period of 30 min at 93°C). The amylose cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…An increase in SO 2 and/or lactic acid concentration or the utilization of proteolytic enzymes could improve the sorghum starch refining process [6][7][23][24]. Starch yields obtained from sorghum in this study are similar or higher than the obtained by Kulkarni et al [25], Watson [5], Watson and Hirata [12] and Wankhede et al [26]. The WWx had a significantly higher starch yields and recoveries at both steeping solutions and times (p < 0.05) than the RS and WHWx.…”
Section: Resultssupporting
confidence: 64%
“…An increase in SO 2 and/or lactic acid concentration or the utilization of proteolytic enzymes could improve the sorghum starch refining process [6][7][23][24]. Starch yields obtained from sorghum in this study are similar or higher than the obtained by Kulkarni et al [25], Watson [5], Watson and Hirata [12] and Wankhede et al [26]. The WWx had a significantly higher starch yields and recoveries at both steeping solutions and times (p < 0.05) than the RS and WHWx.…”
Section: Resultssupporting
confidence: 64%
“…Wild type A-type: Disc-shape (Ellis et al, 1998) B-type: lenticular (Ellis et al, 1998) A-type:10-25 (Ellis et al, 1998) B-type: 5 (Ellis et al, 1998) 0.7-1.2 (Morrison et al, 1984) 0.2-0.4 (Ellis et al, 1998) 19-22.1 (Ellis et al, 1998) 25.3-30.1 (Morrison et al, 1984) Waxy A-type:10-25 (Ellis et al, 1998) B-type: 5 (Ellis et al, 1998) 0.3-0.5 (Morrison et al, 1984) 0.06-0.15 (Ellis et al, 1998) 1.8-3.6 (Ellis et al, 1998) 2.1-8.3 (Morrison et al, 1984) High amylose A-type: 15-32 (Ellis et al, 1998) B-type :2-3 (Ellis et al, 1998) 1.0-1.7 (Morrison et al, 1984) 18.2-24.1 (Ellis et al, 1998) 38.4-44.1 (Morrison et al, 1984) Sorghum Wild type Polygonal, dented and round (Wankhede et al, 1989) 8-14,5 polygonal, 8-10 round (Wankhede et al, 1989) 0.8 (Emmambux & Taylor, 2013) 2.3 (Emmambux & Taylor, 2013) 23.7-27.6 (Boudries et al, 2009) 26-30/A (Boudries et al, 2009) Waxy Larger than normal sorghum (Lawal et al, 2011) 5-25 (Sang et al, 2008) < 0.3 (Sang et al, 2008) 3.5 (Sang et al, 2008) 0 (Sang et al, 2008) Heterowaxy 14 (Sang et al, 2008) …”
Section: Barleymentioning
confidence: 99%
“…Typical gelling temperatures for sorghum starch cover the range 68 -78°C for onset to completion of gelation; this is similar but slightly higher than the range for normal maize starch [39]. Typical pasting temperatures are in the order of 75°C with peak viscosities around 330 BU [39,40]. A comparison of the swelling and solubility properties of sorghum and wheat starch has been carried out by Carcea et al [37] the results are summarized in Figs.…”
Section: Starchmentioning
confidence: 96%
“…A study of the hydrolysis of starch from maize and sorghum using a-amylase [40] has shown that the lower digestibility (l5-25% compared to maize) probably results from affects from the protein, since pre-treatment with a protease before cooking res tores some of the digestibility. The cause of this effect is not obvious since, unlike wheat, the protein matrix around the starch is not continuous but contained in bodies.…”
Section: Starchmentioning
confidence: 98%
See 1 more Smart Citation